The sovereign default risk of giant oil discoveries - Carlos Esquivel (Rutgers University, Department of Economics, 2024)
I study the impact of giant oil field discoveries on default risk. I document that interest rate spreads of emerging economies increase by 1.3 percentage points following a discovery of median size. I develop a sovereign default model with investment, three-sector production, and oil discoveries. Following a discovery, borrowing and investment increase. Capital reallocates from manufacturing toward oil and non-traded sectors, increasing the volatility of tradable income. Borrowing increases default risk and higher volatility increases the risk premium, both of which increase spreads. Discoveries generate welfare gains of 0.44 percent. Insurance against low oil prices increases these gains to 0.60.
Keywords: F34; F41; Q33; 330; Soveriegn default; Oil Discoveries